Pacific poverty, solutions and government response / Greg Clydesdale - Greg, Clydesdale (2014)
Wealth is irregularly distributed and many countries have ethnic minorities that feature disproportionately among the poor. One of the most enduring problems in the New Zealand economy is the persistence of poverty among Pacific people. Government attempts to fix this have failed. In fact numbers living on poverty have grown dramatically. Multi-culturalism is often offered as a solution in preference to assimulation in which the dominant culture imposes its values on minority groups. However, this raises the question whether some degree of assimulation is needed to aquire wealth generating behaviors. This paper examines reasons for government failure to solve Pacific poverty in New zealand and argues that it has failed to identify and address the underlying cause. The cause is a cultural mis-match where Pacific cultural behaviours are not well matched to the demands of the NZ economy. The solution is to focus on the behaviours of parents who are the transmitters of culture.